Real-time PCR quantification of arbuscular mycorrhizal fungi: does the use of nuclear or mitochondrial markers make a difference? - Voříšková, Alena; Jansa, Jan; Püschel, David; Krüger, Manuela; Cajthaml, Tomáš; Vosátka, Miroslav; Janoušková, Martina (Mycorrhiza, 2017)
Root colonization by arbuscular mycorrhizal fungi (AMF) can be quantified by different approaches. We compared two approaches that enable discrimination of specific AMF taxa and are therefore emerging as alternative to most commonly performed microscopic quantification of AMF in roots: quantitative real-time PCR (qPCR) using markers in nuclear ribosomal DNA (nrDNA) and mitochondrial ribosomal DNA (mtDNA). In a greenhouse experiment, Medicago truncatula was inoculated with four isolates belonging to different AMF species (Rhizophagus irregularis, Claroideoglomus claroideum, Gigaspora margarita and Funneliformis mosseae). The AMF were quantified in the root samples by qPCR targeted to both markers, microscopy and contents of AMF-specific phospholipid fatty acids (PLFA). Copy numbers of nrDNA and mtDNA were closely related within all isolates; however, the slopes and intercepts of the linear relationships significantly differed among the isolates. Across all isolates, a large proportion of variance in nrDNA copy numbers was explained by root colonization intensity or contents of AMF-specific PLFA, while variance in mtDNA copy numbers was mainly explained by differences among AMF isolates. We propose that the encountered inter-isolate differences in the ratios of mtDNA and nrDNA copy numbers reflect different physiological states of the isolates. Our results suggest that nrDNA is a more suitable marker region than mtDNA for the quantification of multiple AMF taxa as its copy numbers are better related to fungal biomass across taxa than are copy numbers of mtDNA.
Keywords: buněčné jádro; Real-Time Polymerase Chain Reaction; Microsymbiont screening; Nuclear ribosomal DNA; Molecular genetic quantification; DNA fungální; DNA, Mitochondrial; Plant Roots; Arbuscular mycorrhizal fungi; kvantitativní polymerázová řetězová reakce; kořeny rostlin; Real-time PCR; Cell Nucleus; Mycorrhizae; mykorhiza; Isolate discrimination; PLFA; mitochondriální DNA; DNA, Fungal; Glomeromycota; Medicago truncatula; Mitochondrial DNA